Juvenile myoclonic epilepsy presenting as a new daily persistent-like headache - Rozen, Todd D. (Springer Milan, 2011)
New daily persistent headache (NDPH) is a recognized subtype of chronic daily headache with a unique presentation of a daily headache from onset typically in individuals with minimal or no prior headache history. Various secondary mimics of NDPH have now been documented but at present there has been no association made between primary epilepsy syndromes and new daily persistent-like headaches. A case patient is presented who developed a daily continuous headache from onset who 3 months after headache initiation had her first generalized tonic-clonic seizure. Further investigation into her history and her specific EEG pattern suggested a diagnosis of juvenile myoclonic epilepsy (JME). Her NDPH and seizures ceased with epilepsy treatment. Clinically relevant was that the headache was the primary persistent clinical symptom of her JME before the onset of generalized tonic-clonic seizures. The current case report adds another possible secondary cause of new daily persistent-like headaches to the medical literature and suggests another association between primary epilepsy syndromes and distinct headache syndromes.